FRAUD TRIANGLE SEBAGAI MOTIF NIAT MELAKUKAN KECURANGAN AKADEMIK - lolita hersa rahmadina; Aprina Nuhrahesthy Sulistya Hapsari (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
This study aims to determine the effect of the fraud triangle consisting of pressure, opportunity and rationalization of students' intentions to commit academic fraud. This type of research is quantitative research, using a questionnaire sent via Google froms as a research instrument. The sampling method is convinience sampling method. The population of this research is the S1 Accounting class year 2019 Satya Wacana Christian University and the sample used amounted to 143 respondents. The analytical tool used for testing is multiple linear regression which previously had to pass the classical assumption test. The data used in this study are primary data. Data obtained from respondents were processed using SPSS software version 21. The results of this study indicate that pressure and opportunity have an effect on students' intention to commit academic fraud. Rationalization does not have an influence on students of accounting class 2019 Satya Wacana Christian University to have the intention to commit academic fraud.